Экологическая футурология и возможности ее транскрипции в наши дни - Годзь, Наталья Борисовна (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2016)
Статья посвящена вопросам анализа феномена будущего и проблемам, связанным с теоретической и практической стороной его исследования. Предлагается анализ лингвистического характера понимания и описания, а, следовательно, интерпретации будущего. Автор рассматривает ясное понимание функций и задач как условие, позволяющее ученым и практикам в их моделирующей деятельности более верно увидеть модели будущего с его кризисами и с оптимальными путями их преодоления. Ни понятие "устойчивое развитие", ни его переводы не несут в себе вербальную позитивно мотивирующую нагрузку. Прежний украинский перевод, а именно "Сталий розвиток", и нынешний его вариант "Стійкий розвиток" не мотивирует к поиску и развитию нового мировоззрения по отношению к природе и человеку.

The article is dedicated to the future phenomenon analysis questions and to the problems of its theoretical and practical sides of investigation. There is assumed the analysis of the linguistic character of the future understanding and description that is its interpretation. The author views the clear understanding of the ecology functions and tasks as the condition allowing the scientists and the practitioners in their modeling activity to see more correctly the models of the future as with its crises so with the optimal ways of its overcoming. Neither the concept of “sustainable development” nor its translations don’t bear the positively motivating verbal sense. The previous Ukrainian translation namely “Staliy rosvitok” and the current variant as “Stiykiy rosvitok” don’t motivate for the searching and the development of the new worldview concerning the nature and the human.
The ecological futurology and the opportunities of its transcription nowadays
Keywords: мировоззрение; картина мира; развитие устойчивое; weltanschauung; sustainable development